Notes on the modernization of crafts in Latin America - Lauer, Mirko (1984)
The contemporary handcrafted map of Latin America stems from a historical evolution anchored in demographic factors, and also from diverse relationships with technology and capital. The state-imposed country approach has sought a national perspective on this problem, but has only half achieved it. There is practically no country that is deprived of pointing out that the crafts of its territory are a faithful reflection of national essences, and in a certain way this is true; but deep down, beyond a tribute to nationalist ideology, these two realities lack many points of contact outside of state policies. These are pre-national (or, if you prefer, extra-national) realities.